PEMBERDAYAAN PEREMPUAN MELALUI PELUANG WIRAUSAHA KUDAPAN TRADISIONAL ACEH - Alfi Rahmadi; Cut Risya Varlitya; Vivi Silvia; Fitri Eryanda; Siregar, Latifah Rahayu (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2024)
Traditional Acehnese food is a heritage product that is consumed and served by the Acehnese people during celebrations or certain events and has a unique taste. The community service program aims to provide socialization through the identification of various MSME products and opportunities for traditional Acehnese snacks (kue seupet) to empower women in Gampong Lam Duro, Darussalam, Aceh Besar. The business entrepreneur opportunity of traditional Acehnese snack products (kue seupet) motivated the participants to make it a household business and create a village-leading culinary product to support income and family resilience. Digital marketing and online order receiving have become important to increasing sales. At the end of the community service, a cooking competition for Acehnese cuisine, "kuah pliek u" was successful and memorable, building solidarity with the participants as well as improving their creativity and cooking skills, which can be an idea for selling Acehnese traditional cuisine.